PENINGKATAN KEMAMPUAN KERJA SAMA PESERTA DIDIK MENGGUNAKAN MODEL SMALL GROUP DISCUSSION BERBANTUAN MEDIA GAMBAR DI SEKOLAH DASAR - Dea Ananda Fitri; M. Syahrul Rizal; Yenni Fitra Surya; Iis Aprinawati; Sumianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of cooperation among fourth-grade students in Pancasila Education classes. The purpose of this study was to improve the reading comprehension skills of fourth-grade students at UPT SDN 012 Pasir Sialang. This study is a classroom action research, which was conducted in two cycles, each consisting of two meetings. Based on the results of the research conducted through two cycles, in cycle I meeting 1, the number of students who completed the test was 41% with a very poor category, and in cycle I meeting 2, the number of students who completed the test was 55% with a poor category. In cycle II meeting 1, the number of students who passed increased to 64% with a sufficient category, and in cycle II meeting 2, the number of students who passed was 77% with a good category. Based on the results of this study, it shows that the application of the Small Group Discussion model assisted by pictures can improve the cooperation skills of students in Pancasila education for fourth-grade students at UPT SDN 012 Pasir Sialang.